Utilizing Midtrans as A payment Gateway for Non-Cash Transactions - Mochammad Rizal Aditya; Irwan Alnarus Kautsar (SAGA: Journal of Technology and Information System, 2025)
Increasingly, including payments in school e-canteens. One of the payment methods that can be used is to use a payment gateway such as Midtrans. This study aims to evaluate the use of Midtrans as a payment gateway for noncash transactions in school canteens using the waterfall method. This study uses the waterfall method to develop a payment system using Midtrans in the school canteen e-canteen. Data was collected through interviews with schools and e-canteen users as well as observations of the transaction process using Midtrans. Data analysis was performed using a qualitative descriptive method. This information system was built using the PHP programming language with the MSQL programming language and the Laravel framework using the SDLC (Systems development life cycle) method, which is a method that refers to the models and processes used to develop software systems and describe processes.